On two ways to expand on the harm principle - Castro, Rodrigo Jungmann de (Argumentos - Revista de Filosofia, 2025)
In this article I survey the historical antecedents of what has been commonly referred to as John Stuart Mill´s Harm Principle and some of the ways in which the principle has been discussed in the work of recent analytic philosophers. Subsequently, in the article`s substantive core, I focus entirely on what Mill refers to as the “moral coercion of public opinion”. Here I address matters which I take to underexplored in the literature, namely some difficulties that arise for Mill´s treatment in connection with our ordinary notions concerning politeness and social avoidance. Though the problem of avoidance has been addressed by Dan Threet and John Dilulio, among others, I believe that my approach to the problems created by Mill`s take on politeness is entirely original with me. Considering the foregoing, I propose adding two supplementary clauses to the Harm Principle. I conclude by presenting a modern statement of said principle.